Differential effect on different immune subsets of neoadjuvant chemotherapy in patients with TNBC. Issue 2 (16th November 2020) - Massa, Chiara; Karn, Thomas; Denkert, Carsten; Schneeweiss, Andreas; Hanusch, Claus; Blohmer, Jens-Uwe; Zahm, Dirk-Michael; Jackisch, Christian; van Mackelenbergh, Marion; Thomalla, Jörg; Marme, Frederik; Huober, Jens; et al.
Abstract : Background: Triple-negative breast cancer (TNBC) is the most aggressive form of breast cancer (BC). Due to the absence of targets such as HER2 or hormone receptors, early TNBC is treated with surgery and chemotherapy. Since TNBC is also considered the most immunogenic type of BC with tumor infiltrating lymphocytes that are predictive for chemotherapy response and prognostic for patients′ survival, many different immunotherapeutic strategies are currently explored in clinical trials for the treatment of this disease. In order to efficiently combine chemotherapy with immunotherapy, it is important to evaluate the effect of chemotherapy on immune cells in vivo. Methods: Peripheral blood was taken from 56 patients with TNBC undergoing neoadjuvant chemotherapy with nanoparticle albumin-bound paclitaxel (Nab-Pac) followed by epirubicin and cyclophosphamide (EC) at three different time points. Multicolor flow cytometry was used to characterize the immune cell composition and functional properties along neoadjuvant chemotherapy. Results: Whereas the first phase of the neoadjuvant chemotherapy did not significantly alter the patients′ immune cell composition, after the second phase of chemotherapeutic administration most B cells (>90%) were lost and the frequency of natural killer (NK) cells and CD4 + T lymphocytes decreased approximately to 50%. In contrast, the frequency of CD8 + T cells were less affected. Conclusions: Despite late consequences of Nab-Pac cannot be ruled out, these data suggest that different chemotherapeutics might have distinct effects on the immune cell repertoire and that different immune cell populations exhibit a specific susceptibility to these chemotherapies with B and NK cells being more affected than T cells. This might also have an impact on the combination of chemotherapies with immunotherapies. Trial registration number: NCT02685059 .